Perfil de farmacorresistencia del mycobacterium tuberculosis en pacientes que ingresaron a retratamiento de los establecimientos de las redes de salud bonilla, bepeca y ventanilla, DIRESA Callao, 2006-2010 - Grández Urbina, José Antonio (2013)
Objective: To determine the profile of drug resistance in Mycobacterium tuberculosis retreatment patients admitted to the local health networks Bonilla, Bepeca and Ventanilla, DIRESA Callao, 2006-2010 Materials and Methods: The patients diagnosed with tuberculosis smear (+) and sensitivity to anti-TB drugs that entered re-treatment, sensitivity tests were performed at the National Institute of Health (NIH), were used frequencies of the variables set and used measures of central tendency and dispersion for qualitative variables. Results: The prevalence of drug resistance to one or more drugs was 29%, Multi-resistance was 21%. The overall frequency of isoniazid resistance was 97.34% (n = 404), 81.20% rifampicin (n = 337), streptomycin 46.41% (n = 188). Conclusions: In this study we found that there is a high prevalence of resistant TB in patients admitted to retreat establishments Bonilla, Bepeca and Ventanilla Health networks, , Callao being the most prevalent form of MDR-TB being the most commonly drug resistance genus monoresistencia in patients with isoniazid.